Fundamentalne i techniczne czynniki determinujące kształtowanie cen akcji - Wilimowska, Zofia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Capital investment is an attractive form of the cash surplus investing. Methods of the investment selection consider many factors that create securities prices. Risk is inseparable attribute of an investment; risk understood as a possibility that required effect does not be gained because unpredictability of environmental factors changing. Effectiveness of capital investment depends on investor's ability and his skills to right evaluation of influence of these factors on securities prices. Two methods, technical analysis and fundamental analysis offer tools that are used to solve the problem of investment selection. The methods based on completely different sources of information. The goal of the] paper is to show that using both methods gives better results. In the paper, these two methods are discussed - their advantages and disadvantages and fundamental factors influencing stock prices, A connection of company value and stock pricing is considered additionally. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 602-618